ASSESSMENT OF THE INFLUENCE OF SOCIO-ECONOMIC FACTORS ON FAMILY DIVORCE - Abduramanov Kh.Kh.; Ibragimov Lutfullo Ziyadullaevich; Alimjanova D.M. (Social science and innovation, 2023)
In this article, the impact of socio-economic factors on divorce is analyzed, scientifically based proposals and recommendations are developed for all factors affecting the divorce process